Cancer and tuberculosis: case series - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2010)
Tuberculosis is seen with an increased frequency in cancer patients. Possible reasons of reactivation are thought to be related to chemotherapy and insufficient nutrition together with compromised immune system. The diagnosis of tuberculosis may be missed in cancer patients and may be diagnosed with newly developed radiological and clinical findings during treatment. In this case, tuberculosis should be considered and related diagnostic work up should be completed. Also, PPD test should be applied to cancer patients and if needed isoniazid prophylaxis should be initiated. We present herein 4 cancer patients diagnosed with pulmonary tuberculosis. Two patients suffered from solid malignancies (lung cancer) and 2 from non-solid malignancies (acute myeloid leukemia).
Keywords: cancer; PPD; prophylaxis; tuberculosis; DISEASE